TV white spaces maps computation through interference analysis - Dionísio, Rogério (2015)
“Copyright © [2011] IEEE. Reprinted from ICT Future Network & Mobile Summit 2011. ISBN: 978-1-4577-0928-9. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”